(untitled) (Mongolian Journal of Humanities and Social Sciences, 2023)
This paper employs sociolinguistic methodologies to investigate the distinctive lexical elements within the ööld ethnic groups dispersed across Mongolia as well as Inner Mongolia in People’s Republic of China. Specifically, the study focuses on the ööld communities in various regions, including the Erdenebüren soum of Khovd province and the Ölziit and Ögiinuur soums of Arkhangai Province in Mongolia, as well as the Imin, Bayantal, Aguit, and Bilüüt villages of Imin soum in Inner Mongolia’s Autonomous Prefecture of Hölunbuir, China, predominantly inhabited by ööld groups. The research findings reveal that the utilization of unique ööld dialectal terms varies significantly based on diverse sociocultural factors. These factors encompass distinct geographical locations, socioeconomic class, societal roles, occupational domains, social standing, age brackets, gender dynamics, and the specific interpersonal context in which communication occurs. This study concludes that the presence and usage of ööld-specific vocabulary are intricately linked to the intricate social fabric and contextual intricacies shaping the linguistic expressions within Ööld ethnic groups across different settings and circumstances. Монгол хэлний нутгийн аялгууны үгсийг нийгэм хэл шинжлэлийн үүднээс судлах нь (Өөлд аман аялгууны жишээгээр) Хураангуй: Монгол Улсад тархан суурьшсан өөлд угсаатнууд дундаас ойрад аялгууныхаа аман ярианы өвөрмөц үгсийг хэвээр хадгалан буй Ховд аймгийн Эрдэнэбүрэн сум, халхуудтай хил залган амьдарч буй Архангай аймгийн Өлзийт, Өгийнуур сумын халхажсан өөлдүүд болон БНХАУ-ын Өвөр Монголын Өөртөө Засах Орны Хөлөнбуйр хотын Эвенк Үндэстний Өөртөө Засах Хошууны Имин сумын Баянтал, Агуйт, Имин, Билүүт гэх дөрвөн гацаанд голлон тархан суурьшсан өөлд угсаатнуудын өвөрмөц онцлогтой үгсийг түүвэрлэн авч нийгэм хэл шинжлэлийн аргаар судлав. Дээр дурдсан өөлдүүд харилцан адилгүй газар оронд амьдарч байгаа, нийгмийн давхарга, аж амьдралын хүрээ цараа, нийгэмд эрхэлж буй ажил, албан тушаал, нас, хүйс, харилцаж байгаа этгээд гэх мэт нийгмийн байдлаас шалтгаалан өвөрмөц онцлогтой үгсийн хэрэглээ өөр хоорондоо адилгүй байна. Түлхүүр үг: Өөлд аман аялгууны үгс, Ойрад аман аялгуу, өвөрмөц онцлогтой үгс